Design of Hybrid Hull Ship by B-NINE TEAM to The National Unmanned Fast Boat Contest 2019 - Salmat, Salmat; Zulhendrik, Arya; Iski, Muhammad Iqbal; Adli, Arifin; Nasty, Aulia Zulkanain (Universitas Negeri Padang, 2020)
The Nastional Unmanned Fast Boat Contest 2019 is an event to discover colleger interests and talents about ships and as an event to hone and develop college competitions.B-NINE TEAM from Universitas Negeri Padang is very interested and interested to participating based on illegal fishing problem that occurs. Ship design through literature study and ship model analysis using computer simulations. Ship comparison methods and trial-error to determine the shape of the hull to be userd and numerical experiments.Dimensions of the ship are Length Overall 0.80 m; Length Waterline 0.79 m; Beam 0.05 m; Depth 0.24 m; Draft 0.05 m. The variable parameter used is the variation of catamaran hull type V asymmetric inner flat. There are two types of modification applied, that is modification hull type U asymmetric and modification hull type U symmetric. Based on result of computer simulation testing, based on result of computer simulation testing, it is found that modification hull type U asymmetric has a low resistance value is 5.31 N at a speed of 4.2 knots with effective is 0.04776 Kw and main engine power of 0.1.70 KW.